2018
DOI: 10.1519/jsc.0000000000001931
|View full text |Cite
|
Sign up to set email alerts
|

The Age of Peak Marathon Performance in Cross-Country Skiing—The “Engadin Ski Marathon”

Abstract: Knechtle, B and Nikolaidis, PT. The age of peak marathon performance in cross-country skiing-the "Engadin Ski Marathon." J Strength Cond Res 32(4): 1131-1136, 2018-The age of the best endurance performance has been well investigated in flat city running marathons. However, we have no knowledge about the age of peak marathon performance in cross-country skiing, which would be of great practical value for athletes and coaches. Therefore, the aim of the present study was to examine the age of peak marathon perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…The decreased MWR in the slower performance groups indicated that women were slower than men, which was in line with the sex difference found in another XC skiing race (Engadin ski marathon) [20,24]. The faster race speed in men might reflect sex differences in VO 2 max [17,28], muscle power and body mass [18], because it has been shown that these physiological characteristics are related to performance in XC skiing [7,31].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The decreased MWR in the slower performance groups indicated that women were slower than men, which was in line with the sex difference found in another XC skiing race (Engadin ski marathon) [20,24]. The faster race speed in men might reflect sex differences in VO 2 max [17,28], muscle power and body mass [18], because it has been shown that these physiological characteristics are related to performance in XC skiing [7,31].…”
Section: Discussionsupporting
confidence: 79%
“…We excluded the cases (n = 540) with at least one missing split time, which resulted in the final inclusion of 183,919 finishers (19,465 women and 164,454 men) (▶Table 2). Because there is a sex difference in race time in XC skiing [20,24], we classified finishers in performance groups (nine in women and 10 in men) based on race time ( < 3 h, 3-4 h, …, 11-12 h, > 12 h). The different number of performance groups between women and men was due to the fact that no woman had a race time < 4 h. The number of performance groups into which finishers were assigned was similar to the number of groups used at the start of the official race.…”
Section: Data Sampling and Data Analysismentioning
confidence: 99%
“…The average age of our fast skiers was 26 (the winner was 32), while the corresponding value for the slow skiers was 22. Thus, these fast skiers may have developed their athletic performance [ 19 ], including factors of importance for endurance in skiing such as aerobic capacity, exercise economy, muscle strength and technical skills [ 20 ], to a greater degree. Such development probably allowed them not only to ski at high speed, but also to maintain a high pace throughout the race.…”
Section: Discussionmentioning
confidence: 99%
“…The age in our group (38.69±7.95) was significantly higher than among the best long-distance skiers. According to Knechtle and Nikolaidis [9] the age of peak performance of cross-country skiers competing in long distance races was much lower and closer to the peak of aerobic capacity than what was found in previous studies in marathon road runners. In our study (VO 2 max) it was 48.37 ml/kg/min and 3.83 l/min.…”
Section: Discussionmentioning
confidence: 49%